2021
DOI: 10.3390/polym13081301
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer Bonding Capability of Additively Manufactured Polymer Structures under High Strain Rate Tensile and Shear Loading

Abstract: Additive manufacturing of polymers via material extrusion and its future applications are gaining interest. Supporting the evolution from prototype to serial applications, additional testing conditions are needed. The additively manufactured and anisotropic polymers often show a weak point in the interlayer contact area in the manufacturing direction. Different process parameters, such as layer height, play a key role for generating the interlayer contact area. Since the manufacturing productivity depends on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Of course, the actual shear failure process in this study was extremely complicated; so, our purpose was to promote immediate interest from interdisciplinary researchers. Specifically, not many studies have focused on the shear failure of 3D printing polymers [ 11 , 12 , 13 ]. Our future work will be focused on the shear crack propagation of the same PA12 material, but the specimens will be made with SLS and FDM.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, the actual shear failure process in this study was extremely complicated; so, our purpose was to promote immediate interest from interdisciplinary researchers. Specifically, not many studies have focused on the shear failure of 3D printing polymers [ 11 , 12 , 13 ]. Our future work will be focused on the shear crack propagation of the same PA12 material, but the specimens will be made with SLS and FDM.…”
Section: Resultsmentioning
confidence: 99%
“…With the fast development of additive manufacturing [32,33], our basic research work can be easily used for practical applications. For example, during a multi-material 3D printing process, several polymer layers are printed first, then a DTMI layer is printed before more polymer layers are printed above the DTMI layer.…”
Section: Discussionmentioning
confidence: 99%
“…Simplified contact mechanics analysis showed that the low Young's modulus of the added adhesive layer is one of the key parameters to reducing the maximum impact force in layered polymers, which leads to dynamic crack arrest at interfaces. Therefore, an efficient material design principle was proposed to develop future material sys- With the fast development of additive manufacturing [32,33], our basic research work can be easily used for practical applications. For example, during a multi-material 3D printing process, several polymer layers are printed first, then a DTMI layer is printed before more polymer layers are printed above the DTMI layer.…”
Section: Discussionmentioning
confidence: 99%